2019
DOI: 10.3389/fphys.2019.00751
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine Supplementation Enhances Post Ischemic Hind Limb Revascularization

Abstract: High (millimolar) concentrations of the histidine containing dipeptide – carnosine (β-alanine-L-histidine) are present in the skeletal muscle. The dipeptide has been shown to buffer intracellular pH, chelate transition metals, and scavenge lipid peroxidation products; however, its role in protecting against tissue injury remains unclear. In this study, we tested the hypothesis that carnosine protects against post ischemia by augmenting HIF-1α angiogenic signaling by Fe 2+ chelation. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
(121 reference statements)
0
16
1
Order By: Relevance
“…We must reject the current study’s hypothesis that daily omega-3 fatty acid, β-alanine, and carnosine intakes would correlate with significant amounts of total work variance. Current results, in comparison to positive outcomes seen in related studies [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 ], were unexpected. Throughout the 14-day dietary period, the current study participants were not administered a structured exercise intervention or ingested supplements for the three nutrients under investigation, either of which would have increased the concentrations of those same nutrients [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 ].…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…We must reject the current study’s hypothesis that daily omega-3 fatty acid, β-alanine, and carnosine intakes would correlate with significant amounts of total work variance. Current results, in comparison to positive outcomes seen in related studies [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 ], were unexpected. Throughout the 14-day dietary period, the current study participants were not administered a structured exercise intervention or ingested supplements for the three nutrients under investigation, either of which would have increased the concentrations of those same nutrients [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 ].…”
Section: Discussioncontrasting
confidence: 68%
“…Throughout the 14-day dietary period, the current study participants were not administered a structured exercise intervention or ingested supplements for the three nutrients under investigation, either of which would have increased the concentrations of those same nutrients [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 ]. Yet, in relation to the studies that saw positive outcomes [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 25 ], the inclusion of current study data suggests that the totality of evidence on this topic makes a strong case for dietary supplementation, and the 55% carbohydrate, 30% fat, and 15% protein macronutrient ratio while on an isocaloric diet may not offer enough omega-3 fatty acid, β-alanine, and carnosine for long-term manned space missions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carnosine ( 6 ) is a well-established chelating molecule, capable of binding transition metals [ 61 ]. Indeed, it has been suggested that carnosine can compete for iron(II) with hypoxia-inducible factor 1 alpha (H1F-1α), an iron-dependent proline hydroxylase [ 62 ]. Furthermore, carnosine has previously been demonstrated to form mixed transition metal complexes with glutathione [ 63 ].…”
Section: Intracellular Distribution Of Ironmentioning
confidence: 99%
“…There is no doubt that the presence of carnosine is important for muscle contraction, including that of cardiac muscle [ 59 ]. Recently, it has been suggested that carnosine protects muscle against post ischemia by augmenting HIF-1α angiogenic signalling by iron chelation [ 62 ]. Significantly, methylcarcinine ( Scheme 3 ), a carnosine analogue, lacking iron(II)-chelating capacity, was found to have no effect on HIF-1α activity or the release of vascular endothelial growth factor in complete contrast to carnosine [ 62 ].…”
Section: Carnosine and Histidine—iron(ii) Chelators Of Physiologicmentioning
confidence: 99%